A DESCONSIDERAÇÃO DA PERSONALIDADE JURÍDICA NO MBITO DE APLICAÇÃO DA LEI ANTICORRUPÇÃO - Silva, Marcos Paulo Pugnal da (2020)
Corruption, in its various facets, proves to be a challenge to the Brazilian Public Administration. With the promulgation of Law nº 12.846, of August 1, 2013, the Anti-Corruption Law (LAC), effective froms January 29, 2014, it was possible for the Public